Religiusity of Counselor Candidates in Islamic Counseling: Study of Mixed Methods in Guidance and Counseling Department - Muslikah, Muslikah; Sutoyo, Anwar; Sutikno, Ulung Giri (Universitas Negeri Semarang, 2021)
This research is motivated by religiosity or religious adherence to students as potential counselors in Islamic counseling courses. Religiosity affects how individuals view their problems and life at large. In Islamic counseling, religiosity is a mandatory requirement for counselor candidates to develop so that the counselor can transmit in Islamic counseling services. This research aims to study the religiosity of guidance and counseling students at UNNES. The research sample was taken purposively from students who were taking or had been taking Islamic counseling courses in the guidance and counseling department at UNNES with a total of 100 respondents. This study's data collection techniques include two techniques related to the data to be obtained, namely quantitative and qualitative data. The data collection technique for obtaining quantitative data uses a psychological scale.Â The religiosity scale in this study reveals how high student religiosity is. In addition, to obtain data accuracy to strengthen quantitative data, qualitative data is also needed, collected through a focused group discussion method with two students. The quantitative results showed that the level of spirituality of counselor candidates who took Islamic counseling courses was in the moderate category or was 71%. Meanwhile, the qualitative data shows that several things generally influence the students as candidate Islamic counselors in developing spirituality. These are faith (belief in Allah and pillars of faith), worship such as prayer, fasting, and reading the Al-Qur'an, and experiences such as remembering death, parental advice, and lecturers or listening to the holy verses of the Qur'an.